Assessment of Salivary Cortisol Levels as a Biomarker of Anxiety in Patients Undergoing Minor Oral Surgery - ul Wahab, Noor; Waqar-Un-Nisa, Waqar-Un-Nisa; Yahya, Urooj; Mumtaz, Tayyaba; Khan Kasi, Anum; Ahmed, Syed Zaryab (Journal of Neonatal Surgery, 2025)
Background: Anxiety is a common psychological response among patients undergoing minor oral surgical procedures, often influencing pain perception, treatment outcomes, and overall patient experience. Conventional assessment methods rely on subjective scales, which may not accurately reflect physiological stress. Cortisol, a key hormone released in response to stress, can be measured non-invasively in saliva, offering an objective biomarker for anxiety assessment. Objective: This study aimed to evaluate salivary cortisol levels as a biomarker of anxiety in patients undergoing minor oral surgery and to explore its correlation with subjective measures of anxiety. Methods: A cross-sectional study was conducted on patients scheduled for minor oral surgical interventions. Preoperative anxiety levels were assessed using standardized anxiety scales, followed by collection of unstimulated saliva samples at defined time intervals. Cortisol concentrations were analyzed using enzyme-linked immunosorbent assay (ELISA). Statistical analyses were performed to determine associations between salivary cortisol levels, self-reported anxiety scores, and demographic or clinical variables. Results: Salivary cortisol levels demonstrated a significant rise in patients with higher preoperative anxiety scores. A positive correlation was observed between subjective anxiety ratings and cortisol concentrations (p < 0.05), supporting the utility of salivary biomarkers in objectively identifying stress responses. Age, gender, and type of surgical procedure also influenced anxiety-cortisol dynamics. Conclusion: Salivary cortisol serves as a reliable, non-invasive biomarker for assessing perioperative anxiety in patients undergoing minor oral surgery. Integrating salivary cortisol monitoring with conventional psychological assessments may enhance clinical understanding of patient stress, guide preoperative counseling, and improve overall surgical care